Treatment adherence and self-stigma in patients with depressive disorder in remission - A cross-sectional study - Sedlácková, Zuzana; Kamarádová, Dana; Prásko, Jan; Látalová, Klára; Ocisková, Marie; Ocisková, Marie; Cinculová, Andrea; Kubínek, Radim; Mainerová, Barbora; Tichácková, Anezka; Vrbová, Kristýna (Neuro endocrinology letters, 2015)
OBJECTIVE: A wide range of variables may influence the rate of adherence to treatment. These variables can be associated with the disease itself, method of treatment, patient's personality, environmental factors and therapeutic relationship. Self-stigma is one of the possible factors related to poor adherence. The aim of the study was to find out the relationship between current adherence, discontinuation of medication in the past and self-stigma in stable psychiatric outpatients diagnosed with depressive disorder. METHODS: The study included 72 stable outpatients diagnosed with depressive disorder with a mean age of 49.00 ± 12.56. Disorder severity was assessed using the Clinical Global Impression scale. Adherence was measured by the Drug Attitude Inventory - 10 items (DAI-10) scale and self-stigma by the Internalized Stigma of Mental Illness (ISMI) scale. The data were evaluated in 66 patients. Six patients were excluded because of incompletely filled in questionnaires. RESULTS: The rate of adherence was not associated with gender, education, employment, family burden (family history) or partner status. Current adherence did not differ between patients who arbitrarily discontinued their medication in the past and those who did not. Adherence was significantly positively correlated with patient's age, age at disease onset and the level of self-stigma. CONCLUSIONS: The study results suggest that the level of self-stigma and age of the patient can be very important factors associated with adherence in patients with depressive disorder.
Keywords: Medication Adherence; hodnocení adherence k farmakoterapii; Humans; lidé středního věku; Female; Aged; dospělí; věkové faktory; senioři; lidé; Assessment of Medication Adherence; Social Stigma; indukce remise; Adult; společenské stigma; ženské pohlaví; Depressive Disorder; stupeň závažnosti nemoci; Male; depresivní poruchy; Middle Aged; Remission Induction; Cross-Sectional Studies; Severity of Illness Index; Age Factors; věk při počátku nemoci; mužské pohlaví; Age of Onset; průřezové studie; adherence k farmakoterapii